An Optimality-Theoretic Analysis of Some Phonological Errors Produced by Saudi Female Learners of the English Language - Анхар Ассунітан (Психолінгвістика, 2023)
Purpose. The purpose of this study was to investigate the phonological errors associated with consonant and vowel pronunciation made by Saudi learners of the English language in light of the optimality hypothesis. In addition, transfer and contrastive analysis hypotheses are discussed, which justify why Saudi English language learners make phonological errors.